An integrated strategic framework for priority setting in the Australian vanilla industry - Taghadomi-Saberi, Saeedeh; Yadav, Dakshina; Mazhar, Muhammad Sohail (Frontiers in Sustainable Food Systems, 2023)
Global demand of vanilla, as a natural flavour, is consistently growing. Vanilla is an emerging crop with high potential for Australian growers due to its climatic suitability in some regions, and high domestic and global demand. In this paper, the priorities of Australian vanilla industry are recognised based on the current issues, challenges, and opportunities. We show the priorities and related activities as established through one-on-one interaction and group engagement with industry wide stakeholders to capture a varied range of views. Critical feedback from the industry included the need for structuring an industry association, arrangements that offer training for example on production, postharvest and product diversification, improvements to the linkages between stakeholders, and technical support from research and development agencies. The priorities were ranked by stakeholders according to their importance as follows: a) capacity building, b) harvest and postharvest protocols, c) production procedures and d) selection of better clonal material. Addressing the industry's needs and priorities will ensure its future development is sustainable and economically viable.Policymakers are encouraged to take into account these discerned priorities and the proposed strategies designed to confront the industry's needs and challenges.